Comparison of Cornell and Peguero-Lo Presti Criteria in Electrocardiography to Diagnose Left Ventricular Hypertrophy in Hypertensive Patients at RSUD Tabanan - I Putu Gede Eka Ariawan Suyasa; Agus Prema Jaya Manik Artha; Made Harlina Purnama Sari (Warmadewa University, 2023)
Left ventricular hypertrophy (LVH) is characterized by an abnormal increase in the mass of the left ventricle due to chronic elevated cardiac workload. LVH serves as a preclinical indicator of cardiovascular disease and stands as a robust predictor of cardiovascular morbidity and mortality. Detecting LVH can be achieved through various methods, including electrocardiography (ECG), radiology, and echocardiography. However, the limited availability and affordability of echocardiography underline the crucial role of ECG, especially in healthcare facilities lacking echocardiography capabilities. The primary objective of this study was to establish more precise diagnostic criteria for identifying LVH in hypertensive patients at RSUD Tabanan. This research is an analytical observational study with a cross-sectional design conducted at RSUD Tabanan. The data were extracted from medical records of hypertensive patients who had received treatment at the hospital's cardiology clinic between 2020 and 2022. Among the patients who met the inclusion and exclusion criteria, ECG assessments were conducted to determine the presence of left ventricular hypertrophy (LVH) using the Cornell criteria and Peguero-Lo Presti criteria. Additionally, echocardiography results were reviewed in the patients' medical records. Of the 111 research subjects, 10 (15.15%) subjects had LVH detected based on the Cornell criteria, 30 (45.45%) subjects had LVH detected based on the Peguero - Lo Presti criteria and 66 subjects (59.46%) had LVH detected using the echocardiography examination. The Cornell Criteria had a sensitivity of 15.15%, a specificity of 93.33% and an accuracy of 59.9% while the Peguero–Lo Presti Criteria had a sensitivity of 45.45%, a specificity of 84.44% and an accuracy of 66.2% for diagnosing LVH. The Peguero – Lo Presti criteria have higher accuracy than the Cornell criteria in diagnosing left ventricular hypertrophy in hypertensive patients according to echocardiography.